Annual Report of the Commissioner for Entrepreneurs' Rights at the President of the Russian Federation as a Guarantee of State Protection of the Rights and Legitimate Interests of Business Entities - E. S. Plakhova (Сибирское юридическое обозрение, 2024)
The practice of having ombudsmen in Russia is relatively recent. The branching of this institution into specialized ombudsmen provided a more timely and specific protection of citizens' rights. Their work is impossible without various constitutional and legal instruments, the meaning of which is revealed in this paper. The Institute of the Commissioner for Entrepreneurs' Rights at the President of the Russian Federation exercises its powers in accordance with current legislation. However, there are situations requiring a more timely response to the problems of the business community. The annual report of Commissioner for Entrepreneurs' Rights at the President of the Russian Federation is a form of report combining the results of the activities of the central office and regional business ombudsmen. It also contains statistics, social survey data, a special report including key business problems, a register of systemic issues of Russian business, as well as administrative pressure index, etc. Using these instruments, a business ombudsman can manage his work in numerous regions of the Russian Federation, provide federal business support, conduct international negotiations, maintain international cooperation, and be engaged in educational and teaching activities.   All these prove the relevance of the research.   The purpose of the study is to identify and analyze the means used by the Commissioner for the protection of the rights of entrepreneurs.   The main part of the study presents three instruments: a special section of the annual report “Key business issues in the context of sanctions and structural transformation”, a Register of systemic issues of Russian business, and administrative pressure index. The methodological basis of the study is the methods of analysis, modeling, observation, comparison and others. Currently, due to a well-coordinated functioning mechanism and a wide number of public and expert assistants, a business ombudsman timely and properly solves various business issues. The paper studies the role the means used by a business ombudsman play for the state and specific public authorities.